Heavy chain deposition disease in a case of clear cell renal cell carcinoma- A jack in the box - Abhishek Kumar; Arpita Roychowdhury; Moumita Sengupta; Keya Basu; Anila Abraham; Uttara Chatterjee; Sriranjan Mukherjee (Indian Journal of Pathology and Microbiology)
Renal cell carcinoma (RCC) is the most common subtype of adult renal tumors, and its detection rate in the early stages has been increased in the dawn of advanced imaging modalities. Nephrectomy is the mainstay of treatment; determination of tumor category and staging is the primary concern of oncopathologists. Non-neoplastic renal parenchyma is overlooked majority of times and thus misses the opportunity to detect concomitant medical renal diseases which also predict the renal outcome in the postoperative era. Although any kind of glomerular or extraglomerular pathology may be encountered, vascular changes in the form of arterionephrosclerosis are the commonest one. Here, we take the opportunity to report an unusual association of heavy chain deposition disease (HCDD) with clear cell subtypes of renal cell carcinoma in a 48-year-old male of Indian ethnicity.